Effect of the electrolipophoresis in the lipodystrophy treatment and its influence on lipid profile - Oliveira, Thais Moreira de; Blanco, Priscila Hellen Martinez; Manchini, Priscila; Delbone, Nawhale (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The excess of body adiposity and the hormonal action can lead to the accumulation of adipose tissue in certain parts of the body. The electrolipophoresis is a technique used to treat localized fat, by applying low frequency electrical currents that act directly on the adipocytes and lipids accumulated subcutaneously or epicutaneously. This electrical stimulation causes physiological modifications in the adipocyte, among them the increase in blood flow and cellular metabolism leading to lipolysis. Objective: This study aimed to prove, through the measurement of triglycerides in the blood, which is the most effective method of electrolipophoresis practical application in the promoted lipolysis. Methods: The old female patients aged from 49 to 62 underwent evaluation that measured the body mass index (BMI); perimetry performed with the use of measuring tape of the waist and abdomen region and the realization of abdominal (vertical) skinfold measurement with the use of adipometer. After the evaluation, the volunteers were divided into two groups in which one of them received subcutaneous application of electrolipophoresis equipment (needles) and the other one received epicutaneous electrolipophoresis application (plates). They were positioned and oriented about the procedure and received the practical application of electrolipophoresis (DGM equipment) twice a week for ten sessions of 60 minutes each. The dosage of triglycerides was performed in the first and last session. Results: There was a reduction in all evaluations performed, and a subcutaneous application shows more effective in the treatment of localized fat. Conclusion: With these findings was observed a reduction in abdominal measurement and decreased of triglycerides in the blood thus showing that treatment using plates or electrodes is effective in localized lipodystrophy. Despite the significant reduction of localized adiposity, further studies with more participants and sessions are needed to make this treatment, widely used in clinical practice of Dermato-Functional Physiotherapy, most reliable.